2007
DOI: 10.1074/jbc.m701740200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Caspase-3 Prodomain to Heat Shock Protein 27 Regulates Monocyte Apoptosis by Inhibiting Caspase-3 Proteolytic Activation

Abstract: Caspase-3 is an essential executioner of apoptosis responsible for regulating many important cellular processes, among them the number of circulating monocytes, central players in the innate immune response. The activation of caspase-3 requires its processing from an inactive precursor. Here we show that the small heat shock protein 27 (Hsp27) associates with caspase-3 and protein-protein interaction experiments in vivo and with purified proteins demonstrate a direct interaction between Hsp27 and the amino-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(151 citation statements)
references
References 36 publications
7
142
1
1
Order By: Relevance
“…For example, HSP27 can inhibit apoptosis by reducing caspase activity (33), decrease cytochrome c release from mitochondria (34), and/or inactivate the apoptosis signal-regulating kinase 1/JNK prodeath signaling cascade (17). A number of previous studies reported the neuroprotective effects of HSP27 against cerebral I/R injury when globally expressed in the brain (15)(16)(17)22).…”
Section: Discussionmentioning
confidence: 99%
“…For example, HSP27 can inhibit apoptosis by reducing caspase activity (33), decrease cytochrome c release from mitochondria (34), and/or inactivate the apoptosis signal-regulating kinase 1/JNK prodeath signaling cascade (17). A number of previous studies reported the neuroprotective effects of HSP27 against cerebral I/R injury when globally expressed in the brain (15)(16)(17)22).…”
Section: Discussionmentioning
confidence: 99%
“…42 However, other possible anti-apoptotic proteins could associate with the prodomain of caspase-6 in an analogous manner to the association of Hsp27 with the prodomain of caspase-3, which results in the inhibition of the autocatalytic processing of caspase-3 from its p20 to its p17 form that is required for its efficient processing and activation. 43 In summary, in contrast to the established model using dATP-activated cell lysates, caspase-7 in addition to caspase-3 can directly process caspase-6, and subsequently the processed caspase-6 can directly process caspase-8. Reagents.…”
Section: Discussionmentioning
confidence: 99%
“…Procaspase-3 Activation Assay-CHO cells were lysed with lysis buffer (Cell Signaling) containing a protease inhibitor mixture, as previously described (28). The extracts were centrifuged for 10 min at 14,000 ϫ g, boiled for 5 min at 100°C, and analyzed by SDS-PAGE and immunoblotting using anti-␤-tubulin antibody (Santa Cruz, CA) or antibodies for inactive caspase-3 (9665S, clone 8G10) and active caspase-3 (9661S, clone Asp 175 ).…”
Section: Methodsmentioning
confidence: 99%